Contribution of Principal leadership, School Climate, andCompensation toward Teacher's Professionalism (A SiteStudy at Junior High School Sub Rayon Weleri, Kendal) - Himam, Muhitul (2012)
The objectives of this study is to analyze and test: First, the contribution of principal leadership, school climate and compensation toward teacher's professionalism at Junior High School Sub Rayon Weleri, Kendal; Second, the contribution of principal leadership toward teacher's professionalism at Junior High School Sub Rayon Weleri, Kendal; Third, the contribution of school climate toward teacher's professionalism at Junior High School Sub Rayon Weleri, Kendal; Fourth the contribution of compensation toward teacher's professionalism at Junior High School Sub Rayon Weleri, Kendal. This research uses a quantitative approach with correlational teechnique. Population of this research are the principal, teacher, and all staff of Junior High School Sub Rayon Weleri, Kendal, and taking of sample which is based on the teachers who has been certified using proportional random sampling. Data collection tool used in this research is questionnaire. Data analysis technique used multiple linear regression with prerequisite test of data analysis such as normality test, multicolinearity test and heteroscedasticity test. The result of this research shows that 1) There is a significant contribution between the principal leadership, teacher' professional competence, school climate and infrastructure toward teacher's professionalism of Junior High School Sub Rayon Weleri Kendal. It is shown by the number of Fcount is 19.750, with the significance value of 0.000 < 0.05, the significant on a 1%. With R2 value of 0.376 give a meaning that 37.6% of independent variable can explain the professionalism of teacher. The rest, 62.4% comes from outside the OLS model; 2) There is a significant contribution between the principal leadership toward teacher's professionalism of Junior High School Sub Rayon Weleri Kendal. It is shown by the number of sig equals to 0.030 < 0.05; 3) There is a significant contribution between the school climate toward teacher's professionalism of Junior High School Sub Rayon Weleri, Kendal, which is shown from the number of sig equals to 0.000 < 0.05; 4) There is a significant contribution between the compensation toward teacher's professionalism of Junior High School Sub Rayon Weleri, Kendal which is shown by the number of sig equals to 0.040 < 0.05.